Does Listening to Music With an Audio Ski Helmet Impair Reaction Time to Peripheral Stimuli? - Ruedl, G.; Pocecco, E.; Wolf, M.; Schöpf, S.; Burtscher, M.; Kopp, M. (International Journal of Sports Medicine, 2012)
With the recent worldwide increase in ski helmet use, new market trends are developing, including audio helmets for listening to music while skiing or snowboarding. The aim of this study was to evaluate whether listening to music with an audio ski helmet impairs reaction time to peripheral stimuli. A within-subjects design study using the Compensatory-Tracking-Test was performed on 65 subjects (36 males and 29 females) who had a mean age of 23.3±3.9 years. Using repeated measures analysis of variance, we found significant differences in reaction times between the 4 test conditions (p=0.039). The lowest mean reaction time (±SE) was measured for helmet use while listening to music (507.9±13.2 ms), which was not different from helmet use alone (514.6±12.5 ms) (p=0.528). However, compared to helmet use while listening to music, reaction time was significantly longer for helmet and ski goggles used together (535.8±14.2 ms, p=0.005), with a similar trend for helmet and ski goggles used together while listening to music (526.9±13.8 ms) (p=0.094). In conclusion, listening to music with an audio ski helmet did not increase mean reaction time to peripheral stimuli in a laboratory setting.
Keywords: ski helmet; listening to music; peripheral vision; reaction time; alpine skiing; ski injury